Bantenese Language Maintenance A Sociolinguistic Perspective - Erika Rizqiana; Upit Hasanah; Mufidah; Eneng Liah Khoiriyah (Hikamatzu | Journal of Multidisciplinary, 2025)
This study explores the maintenance of the Bantenese language, a Javanese dialect spoken in Banten Province, Indonesia, from a sociolinguistic perspective. It examines the factors contributing to both the continued use and the potential decline of Bantenese, considering its relationship with standard Javanese and the influence of national Indonesian. The research investigates the sociolinguistic variables impacting language choice among different age groups and social strata within the Bantenese community. Findings highlight the role of language attitudes, media exposure, and educational policies in shaping language maintenance strategies and the overall vitality of Bantenese in the face of linguistic globalization. The study concludes by offering recommendations for effective language preservation initiatives, emphasizing the importance of community involvement and culturally relevant language programs.